EFFECTIVENESS OF FREE DELIVERY FOR MEMBERS: AN EMPIRICAL INVESTIGATION OF CONSUMER PURCHASING BEHAVIOR AND REVENUE CONTRIBUTION - Fitrianti, Nida Garnida; Yolistina , Anggun; Haryaman, Adang (Yayasan Kreatif Indonesia Emas, 2024)
Free shipping for members has become a common strategy used by companies to increase sales and customer loyalty. This study aims to investigate the effectiveness of free shipping for members in influencing consumer purchasing behavior and company revenue contribution. Using a combined approach between literature review and empirical analysis, we collected data from various relevant studies and carried out statistical analysis of sales data and profit margins from companies that implement free shipping policies. Our findings show that free shipping for members has a positive impact on consumer purchase frequency, the number of items purchased in each transaction, average order value, and overall company sales. However, the impact on a company's profit margin needs to be carefully considered, as the additional costs associated with this policy can reduce profit margins if not offset by a sizable increase in sales. Based on our findings, we recommend that companies segment customers to better understand their preferences and purchasing behavior, conduct periodic performance evaluations of free shipping policies, and consider incentive alternatives to free shipping to provide variety and flexibility in their marketing strategies.